Technological Resources Used in Virtual Learning and Coping Strategies of Nursing Students - Reymarc P. Galiendo; Christopher Lee R. Castro; Revecca B. Comillas; Daniella Kate A. Delos Santos; Jimboy D.C De Luna; Princess Mae C. Manangan; Cheena Mallari; Zuzette Catabona (Proceedings Series on Health & Medical Sciences, 2021)
The COVID-19 pandemic in the Philippines caused schools to shift from face-to-face learning to a flexible learning approach that partly requires technology to deal with. Given this solution, the implementation caused struggles for nursing students with limited technological resources. Thus, the researchers deemed it necessary to conduct this research to describe the technological resources used by the nursing students and the coping strategies they develop to manage their situation. This research used a quantitative descriptive-correlational approach; a total enumeration as sampling design gathered through questionnaire was utilized. Analysis of data revealed that most of the profile of respondents were female, from the rural area, monthly family income belonged to the low-income group (but not poor), the monthly budget for internet Php 1,001 to Php 1,500, and using a router. The result also showed that students get stressed out when they get disconnected in the online discussion. They also felt pressure in their academic subjects, resulting in ineffective learning and trouble uploading videos. Given these, the student’s coping strategy is to download the PPT/PDF of the online lessons to manage the situation. Correlation analysis was used and revealed that all variables were correlated to each other. This study came up with a proposed program to augment limited technological resources with the aid of the school and in collaboration with other agencies that can address this concern.